2012
DOI: 10.1111/j.1365-2222.2011.03934.x
|View full text |Cite
|
Sign up to set email alerts
|

The 2S albumin allergens of Arachis hypogaea, Ara h 2 and Ara h 6, are the major elicitors of anaphylaxis and can effectively desensitize peanut‐allergic mice

Abstract: Background Ara h 2 and Ara h 6, co-purified together in a 13-25 kD fraction (Ara h 2/6; 20 kD fraction) on gel filtration chromatography, account for the majority of effector activity in a crude peanut extract (CPE) when assayed with RBL SX-38 cells sensitized with IgE from human peanut allergic sera. Objectives To determine if Ara h 2/6 are the primary peanut allergens responsible for allergic reactions in vivo and to determine if Ara h 2/6 would be sufficient to prevent allergic reactions to a complete CPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 30 publications
5
67
0
Order By: Relevance
“…A previous report found that Ara h 2 treated with trypsin/chymotrypsin displayed minimal reduction in IgE binding capacity, and mediator release from rat basophilic leukemia cells was not reduced by protease treatment, which was attributed to the proteolytic resistant core of Ara h 2 [23]. Additionally, studies have examined the effector activity of the peanut 2S albumins, Ara h 2 and 6, and have demonstrated that these proteins are the most potent peanut allergens in terms of degranulating basophils [7] and inducing anaphylaxis in a mouse model of peanut allergy [25]. Our current data show Ara h 2 fragments are present following any of the enzymatic hydrolyses, and thus may account for the persistent basophil reactivity we measured in response to the hydrolysates.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report found that Ara h 2 treated with trypsin/chymotrypsin displayed minimal reduction in IgE binding capacity, and mediator release from rat basophilic leukemia cells was not reduced by protease treatment, which was attributed to the proteolytic resistant core of Ara h 2 [23]. Additionally, studies have examined the effector activity of the peanut 2S albumins, Ara h 2 and 6, and have demonstrated that these proteins are the most potent peanut allergens in terms of degranulating basophils [7] and inducing anaphylaxis in a mouse model of peanut allergy [25]. Our current data show Ara h 2 fragments are present following any of the enzymatic hydrolyses, and thus may account for the persistent basophil reactivity we measured in response to the hydrolysates.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, these 2S albumins are the most seroprevalent in specific IgE immunoassays and the more potent ones in triggering effector cell activation in vitro and positive skin prick test in allergic patients (27,33,48,(49)(50)(51)(52)(53). Both Ara h 2 and Ara h 6 have been shown to be resistant to enzymatic digestion (54)(55)(56).…”
Section: A C B Dmentioning
confidence: 99%
“…To explore this hypothesis, we developed an assay to measure the transient presence of allergen in the blood after intragastric gavage. Several Ara h proteins have been identified as the immunodominant allergens of PN (Arachis hypogaea) (20). We used sensitive capture ELISAs to measure the concentration of two of these proteins in the systemic circulation.…”
Section: Clostridia Colonization Activates Innate Immune Genes In Intmentioning
confidence: 99%